Rocking the Boat: Damage to Eelgrass by Swinging Boat Moorings - Unsworth, Richard K. F.; Williams, Beth; Jones, Benjamin L.; Cullen-Unsworth, Leanne C. (Frontiers in Plant Science, 2017)
Seagrass meadows commonly reside in shallow sheltered embayments typical of the locations that provide an attractive option for mooring boats. Given the potential for boat moorings to result in disturbance to the seabed due to repeated physical impact, these moorings may present a significant threat to seagrass meadows. The seagrass Zostera marina (known as eelgrass) is extensive across the northern hemisphere, forming critical fisheries habitat and creating efficient long-term stores of carbon in sediments. Although boat moorings have been documented to impact seagrasses, studies to date have been conducted on the slow growing Posidonia species’ rather than the fast growing and rapidly reproducing Zostera marina that may have a higher capacity to resist and recover from repeated disturbance. In the present study we examine swinging chain boat moorings in seagrass meadows across a range of sites in the UK to determine whether such moorings have a negative impact on the seagrass Zostera marina at the local and meadow scale. We provide conclusive evidence from multiple sites that Zostera marina is damaged by swinging chain moorings leading to a loss of at least 6ha of UK seagrass. Each swinging chain mooring was found to result in the loss of 122m2 of seagrass. Loss is restricted to the area surrounding the mooring and the impact does not appear to translate to a meadow scale. This loss of UK seagrass from boat moorings is small but significant at a local scale. This is because it fragments existing meadows and ultimately reduces their resilience to other stressors. Boat moorings are prevalent in seagrass globally and it is likely this impairs their ecosystem functioning. Given the extensive ecosystem service value of seagrasses in terms of factors such as carbon storage and fish habitat such loss is of cause for concern. This indicates the need for the widespread use of seagrass friendly mooring systems in and around seagrass.